2022
DOI: 10.3390/ijerph19148414
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Instagram Addiction among University Students during the COVID-19 Pandemic: The Bidirectional Mediating Role of Loneliness

Abstract: Social isolation during the lockdown, and the greater use of online platforms to connect with other people, can alter the dynamic relationship between loneliness, social media use, and subjective well-being. The study examines the mediating role of loneliness in the bidirectional association between Instagram addiction and life satisfaction. Methods: A sample of 954 university students from Poland were enrolled in a cross-sectional online study during the second wave of the COVID-19 pandemic. Participants aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
(254 reference statements)
0
2
0
Order By: Relevance
“…The results of our study show that social media addiction is a common problem with 1.6% of our respondents being at high risk of social media addiction, 37.18% of men using the Internet more than 4 h daily, and 8.83% of men feeling that excessive social media use has a negative impact on their relationship. Rogowska et al revealed that 17.19% of Polish students are addicted to Instagram [19]. It is curious to note that in Rogowska et al research the adverse consequences of Instagram addiction on life satisfaction were identified specifically among female students, while no such effect was observed among their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study show that social media addiction is a common problem with 1.6% of our respondents being at high risk of social media addiction, 37.18% of men using the Internet more than 4 h daily, and 8.83% of men feeling that excessive social media use has a negative impact on their relationship. Rogowska et al revealed that 17.19% of Polish students are addicted to Instagram [19]. It is curious to note that in Rogowska et al research the adverse consequences of Instagram addiction on life satisfaction were identified specifically among female students, while no such effect was observed among their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…3 Aggressiveness in the mediation analyses between the depressive symptomatology and problematic social networking use and external factors, including social isolation, decreased community engagement, and loneliness [26,[60][61][62][63]. In turn, the impact of SM use on mental wellbeing/illness is influenced by several factors such as use modality (occasional vs. excessive), users' age and gender, intrinsic and extrinsic motivations in SM use (e.g., to manage impressions, to share emotions, to reduce loneliness feelings, to increase social connectedness) [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The BFAS scale was translated into several languages, including Polish [ 78 , 81 , 82 ], and research has demonstrated the excellent psychometric properties of the scale and its usefulness in assessing crucial diagnostic criteria of addiction [ 80 ]. The scale was previously modified by the authors of BFAS [ 26 , 78 , 83 ], and adapted versions were used in several other studies to assess addiction to various types of social media [ 6 , 68 , 84 , 85 , 86 , 87 ]. The adaptation (BSMAS) consisted of replacing the word “Facebook” in the instructions with a word denoting another social media (e.g., Instagram, Twitter, TikTok).…”
Section: Methodsmentioning
confidence: 99%